Pyogenic Sacroiliitis and Pyomyositis in a Patient with Systemic Lupus Erythematous - Wafa Chebbi; Saida Jerbi; Wassia Kessomtini; Asma Fradi; Baha Zantour; Mohamed Habib Sfar (Case Reports in Rheumatology)
Pyogenic sacroiliitis and pyomyositis are uncommon infectious diseases and their diagnoses are often delayed. They are typically seen in children and young adults and are rare in middle-aged people especially in those affected by rheumatic diseases. We present the first case of a Staphylococcus aureus related pyogenic sacroiliitis associated with iliacus and gluteal pyomyositis occurring in a patient with systemic lupus erythematosus. Antibiotic treatment was administered for a total of 6 weeks with a total recovery. Pyogenic sacroiliitis and pyomyositis, although remaining rare events, should be remembered as severe complications in immunosuppressed patients with inflammatory diseases. Early clinical suspicion, imaging diagnosis, and adequate therapy are decisive for the satisfactory outcome.